Remittance inflows, financial inclusion, and economic development: An empirical analysis of the world sample - Chuc Anh Tu; Nguyet Thi Minh Phi; Le Quoc Tuan; Naoyuki Yoshino; Tapan Sarker; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2019)
The main purpose of this paper is to empirically investigate the impacts of remittance inflows, financial inclusion, and economic development and whether inward remittances may help to construct an inclusive financial system. Using both endogeneity-robust generalized method of moments and a structural equation model, our results show that remittances and financial inclusions are engines of growth in countries of different income groups. This implies that the policies to attract extra inward remittances and improve financial inclusion status are of great importance and could pull middle-income countries out of middle-income traps. To this end, our empirical study helps to shed light on the development dilemma of remittance inflows and financial inclusion and to explain both direct and indirect mechanisms through which these effects may happen.
Keywords: G00; F24; F63; 330; remittance; financial inclusion; economic development; structural equation model; middle-income countries